2013
DOI: 10.1016/j.apmr.2012.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Complex Versus Simple Activity of Daily Living Staging: Validation of Simple Stages

Abstract: OBJECTIVE To compare simple activities of daily living (ADL) staging with complex ADL staging and to assess the face, construct and predictive validity of simple ADL stages. Activities of Daily Living (ADL) staging is an innovative, partially hierarchical approach to ADL difficulty measurement. Initial staging validation studies used four-level responses to ADL difficulty questions to derive stages (complex ADL staging). Simple ADL stages are based on two-level responses to ADL difficulty questions. DESIGN A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…ADL stages differentiate among people with no activity limitations (stage 0) through total limitations in all ADLs (stage IV). Initially derived in the Second Longitudinal Study of Aging II dataset and shown to be associated with a variety of outcomes (Henry- Sanchez et al 2012;Stineman et al 2012a,b;Sch€ ussler-Fiorenza et al 2013), stages were re-derived for the MCBS population (Stineman et al 2014). Definitions for stages 0, I, II, and IV conform to an ontological order of expected patterns of difficulty documented in the literature (Katz et al 1963;Lawton and Brody 1969;Linacre et al 1994;Saliba et al 2000) and are defined by the specific ADLs a person is able to do (Table 1).…”
Section: Activities Of Daily Living Stagingmentioning
confidence: 99%
“…ADL stages differentiate among people with no activity limitations (stage 0) through total limitations in all ADLs (stage IV). Initially derived in the Second Longitudinal Study of Aging II dataset and shown to be associated with a variety of outcomes (Henry- Sanchez et al 2012;Stineman et al 2012a,b;Sch€ ussler-Fiorenza et al 2013), stages were re-derived for the MCBS population (Stineman et al 2014). Definitions for stages 0, I, II, and IV conform to an ontological order of expected patterns of difficulty documented in the literature (Katz et al 1963;Lawton and Brody 1969;Linacre et al 1994;Saliba et al 2000) and are defined by the specific ADLs a person is able to do (Table 1).…”
Section: Activities Of Daily Living Stagingmentioning
confidence: 99%
“…Activities of daily living (ADL) limitations were expressed as five partially hierarchical and mutually exclusive stages ranging from no difficulty in any ADLs (Stage 0) to difficulty with all ADLs (Stage IV). The initial validation studies of ADL stages were performed with the Longitudinal Study of Aging II sample [ 21 23 ] and were re-derived in the MCBS community sample [ 24 ]. Community participants were asked: “Because of a health or physical problem, (do you/participant if proxy interview) have any difficulty [by (yourself/himself/herself) and without special equipment] with the following: bathing or showering, dressing, eating, getting in or out of bed or chairs, walking, and using the toilet.” Those who reported having difficulty or who did not do the activity because of a health problem were considered to have difficulty.…”
Section: Methodsmentioning
confidence: 99%
“…To test the concept, ADL and IADL stages were initially derived from the Second Longitudinal Study of Aging (LSOA II) because these legacy data contained an exceptionally rich set of person-and environmental-level variables appropriate to testing construct and predictive validity. Higher stages of ADL and/or IADL limitation were associated with logical patterns of comorbidities, perceptions of unmet need for home environmental modifications, history of multiple falls, difficulties inside the home, difficulties entering or leaving the home, urinary and fecal incontinence, hospitalization in the previous month, greater risks of nursing home placement within a 2-year period, and higher 1-, 5-, and 10-year mortality [10][11][12][13][14][15]. Perceived unmet needs for home accessibility features, advanced age, and the presence of conditions expected to be progressively disabling, such as arthritis, predicted decline to higher stages of limitation over 2 years [16].…”
Section: Introductionmentioning
confidence: 99%